2010
DOI: 10.1111/j.2042-3306.2010.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and antioxidant status in intensely exercising horses administered nutraceutical extracts

Abstract: SummaryReasons for performing study: Many nutraceuticals are used as equine supplements without their efficacy having been scientifically tested. Black tea, cranberries, orange peel and ginger are a few of those nutraceuticals that warrant further study. Objective: To test the effects of single doses of black tea, cranberry, orange peel and ginger extract on markers of oxidative stress and antioxidant status following exercise in horses. Methods: In Study 1, 9 mature, healthy but unfit Standardbred mares were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Lipid peroxidation generates a variety of relatively stable decomposition end-products, mainly α, β-unsaturated reactive aldehydes, such as malondialdehyde (MDA) and isoprostanes [11][12][13], which can then be measured as an indirect index of oxidative stress. Reported results on oxidative stress in horses in the literature were mainly based on the exercise physiology [14][15][16]. Anti-oxidant therapies are now designed to prevent oxidative stress which could potentially have significant impact on age-related diseases [17].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation generates a variety of relatively stable decomposition end-products, mainly α, β-unsaturated reactive aldehydes, such as malondialdehyde (MDA) and isoprostanes [11][12][13], which can then be measured as an indirect index of oxidative stress. Reported results on oxidative stress in horses in the literature were mainly based on the exercise physiology [14][15][16]. Anti-oxidant therapies are now designed to prevent oxidative stress which could potentially have significant impact on age-related diseases [17].…”
Section: Introductionmentioning
confidence: 99%
“…Smarsh et al (2010) [16] tested various nutraceuticals in exercising horses and concluded that a single dose did not produce an effect on either oxidative stress or antioxidant status. Selenium supplementation affected mare and foal plasma, muscle and colostrum Se concentrations, but not GPx activity [17].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, single doses of extracts from black tea, orange peel, cranberry, and ginger do not seem able to influence the oxidative stress and the antioxidant status in intensely exercising horses, even if, according to the authors in [28], long-term supplementation would be necessary to investigate whether these extracts may reduce the oxidative stress.…”
Section: Discussionmentioning
confidence: 99%